GRAIN-BOUNDARY SULPHUR SEGREGATION AND EMBRITTLEMENT OF HIGH-PURITY NICKEL - Ilyin, A.M.; Borisov, B.A. (Хабаршы. Физика сериясы, 2018)
Sulphur grain boundary segregation in vacuum-melted nickel of a special production probe were studied by Auger Electron Spectroscopy. Heat-treated samples of high-purity Ni  were electrolytically deuterium doped and fractured by tension and measuring the mechanical characteristics in the ultra-high-vacuum chamber of a special auger-electron spectrometer.